1995
DOI: 10.2176/nmc.35.17
|View full text |Cite
|
Sign up to set email alerts
|

Cavernous Sinus Invasion by Pituitary Adenomas

Abstract: The relationship between magnetic resonance (MR) imaging findings and histologically verified invasion of the cavernous sinus by tumor cells was studied in 26 patients treated surgically for pituitary adenoma. Dural invasion of the sellar floor by tumor cells was found in 10 cases (38%). All patients were classified according to MR imaging findings into three types. Type I showed a gadolinium-enhanced stripe medial to the carotid artery (5 patients), none of which showed dural invasion. Type II showed no enhan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…5,12,1921 Data from these studies demonstrated that extrapituitary tumor invasion of surrounding sella dura could be frequent (24%–94%) and that increasing tumor size as well as age is directly associated with the incidence of invasion. 5,12,19,21 Further, the data showed that dural invasion was associated with incomplete tumor removal and recurrence. 12 While these studies provided important information about the incidence of adenoma-associated dural invasion, they were limited by several methodological factors that have made it difficult to draw direct conclusions related to the precise origin and incidence of this pathological feature in CD.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…5,12,1921 Data from these studies demonstrated that extrapituitary tumor invasion of surrounding sella dura could be frequent (24%–94%) and that increasing tumor size as well as age is directly associated with the incidence of invasion. 5,12,19,21 Further, the data showed that dural invasion was associated with incomplete tumor removal and recurrence. 12 While these studies provided important information about the incidence of adenoma-associated dural invasion, they were limited by several methodological factors that have made it difficult to draw direct conclusions related to the precise origin and incidence of this pathological feature in CD.…”
Section: Discussionmentioning
confidence: 99%
“…5,12,1921 First, all previous reports of pituitary adenoma–associated dural invasion were based on retrospective case series, and most examined nonconsecutive specimens. 5,12,1921 This resulted in a selection bias in which only patients with sites of apparent invasion during surgery 12,21 and/or primarily macroadenomas (most ACTH-positive adenomas are microadenomas) were included in the analysis. 5,12,20,21 Second, in previous studies of anterior dura samples, 12 the sample was coagulated.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This finding is clinically and biologically relevant, and is most probably the consequence of better surgical visualization provided by an endoscope: the improved possibility of visually checking the medial wall of the cavernous sinus intraoperatively, behind the cavernous ICA loop, has shown that the medial wall can be frequently displaced and not invaded in grade 3A PAs; in other cases, it can be spontaneuosly dehiscent and provide a natural corridor for extension of PAs in the cavernous sinus [62]. Other radiological classifications, which include features of the previous ones, have been suggested to attempt an in detail analysis of PA extensions [110], or provide a radiological pathology-specific grading [83,[111][112][113][114].…”
Section: Radiological Criteria and Classificationsmentioning
confidence: 99%